Framing Migration Through the Crisis Era 2015–2022: A Content and Semantic Network Analysis of the Greek Press - Andreas Kollias; Fani Kountouri; Sofia Kalamanti (Journalism and Media)
Since the 2015 refugee crisis, when over 850,000 refugees and migrants reached European shores, migration has sparked intense political and social debates that dominate Europe’s political and media agenda. As a key entry point for refugees and migrants, Greece plays a central role in this ongoing crisis. This study examines how migration has been framed in three major Greek news outlets from 2015 to 2022. This study is groundbreaking as it goes beyond analyzing how mainstream media portray migration, migrants, and refugees. It also examines how the media frame the rhetoric and actions of far-right and right-wing populist parties in relation to migration, offering a more comprehensive and nuanced perspective. Analyzing 9840 opinion articles, it identifies two dominant frames: (a) a ‘political threat’ frame, reflecting concerns over the rise of the far-right in Europe driven by anti-migration rhetoric, and (b) a dual ‘security-humanitarianism’ frame, highlighting tensions between security needs and the imperative to uphold the human rights of refugees and immigrants, reflecting broader societal anxieties. The existence of a political threat frame and a dual-identity frame leads to question the prior conceptualization of security threats and strictly segregated frames in prior literature regarding established framing practices on migration.